Different Compression Techniques Used for Different Applications: Comparing the Performance of Various Data Compression Algorithms for Text Data (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Data compression is a technique use to compress data. It is a process which reduce the size of data by reducing redundant data from it. Hence choosing the best machine learning algorithm is really important. In addition to different compression technologies and methodologies, selection of a good data compression tool is most important. There is a complete range of different data compression techniques available such that it becomes really difficult to choose which technique serves the best. Here comes the necessity of choosing the right method for text compression purposes and hence an algorithm that can reveal the best tool among the given ones. In this paper we represent different algorithms for different applications to compress the text data.